Leadership in politics and science within the Antarctic Treaty - Dudeney, John R; Walton, David W H (Polar Research, 2012)
For over 50 years the Antarctic has been governed through the Antarctic Treaty, an international agreement now between 49 nations of whom 28 Consultative Parties (CPs) undertake the management role. Ostensibly, these Parties have qualified for their position on scientific grounds, though diplomacy also plays a major role. This paper uses counts of policy papers and science publications to assess the political and scientific outputs of all CPs over the last 18 years. We show that a subset of the original 12 Treaty signatories, consisting of the seven claimant nations, the USA and Russia, not only set the political agenda for the continent but also provide most of the science, with those CPs producing the most science generally having the greatest political influence. None of the later signatories to the Treaty appear to play a major role in managing Antarctica compared with this group, with half of all CPs collectively producing only 7% of the policy papers. Although acceptance as a CP requires demonstration of a substantial scientific programme, the Treaty has no formal mechanism to review whether a CP continues to meet this criterion. As a first step to addressing this deficiency, we encourage the CPs collectively to resolve to hold regular international peer reviews of their individual science programmes and to make the results available to the other CPs. Keywords: Governance; claimant states; Antarctic policy; scientific publications.
Keywords: Antarktis; Antarktistraktaten; forvaltning; politikk; vitenskap

Perspective: Strategic challenges of tourism development and governance in Antarctica: taking stock and moving forward - Lamers, Machiel; Liggett, Daniela; Amelung, Bas (Polar Research, 2012)
Keywords: Antarktis; forvaltning; turisme